"The wife of Lucifer" : women and evil in Charles Dickens - Ebelthite, Candice Axell (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2002)
This thesis examines Dickens's presentation of evil women. In the course of my reading I discovered that most of the evil women in his novels are mothers, or mother-figures, a finding which altered the nature of my interpretation and led to closer examination of these characters, rather than the prostitutes and criminals who may have been viewed negatively by Nineteenth century society and thereby condemned as evil. Among the many unsympathetically portrayed mothers and mother-figures in Dickens's works, the three that are most interesting are Lady Dedlock, Miss Havisham, and Mrs Skewton. Madame Defarge initiates the discussion, however, as a seminal figure among the many evil women in the novels. Psychoanalytical and socio-historic readings grounded in Nineteenth century conceptions of womanhood provide background material for this thesis. Though useful and informative, however, these areas of study are not sufficient in themselves. The theory that shapes the arguments of this thesis is defined by Steven Cohan, who argues strongly that the demand for psychological coherence as a requisite of character obscures the imaginative power of character as textual construct, and who both refutes and develops character theory as it is argued by Baruch Hochman. Cohan's theory is also finally closer to that outlined by Thomas Docherty, who provides a complex reading of character as ultimately "unknowable".
Keywords: Dickens, Charles, 1812-1870 -- Characters -- Women; Evil in literature; Women in literature